Alveolar soft part sarcoma of the pectoralis mimicking a breast mass: A case report - Kevin L. Lu; Ryan Sieberg; Rita I. Freimanis; Heather I. Greenwood; Christopher J. Schwartz (Human Pathology Reports, 2022)
Alveolar soft part sarcoma (ASPS) is a potentially lethal soft tissue tumor with a xropensity for distant metastasis. We report an exceedingly rare case of an ASPS arising from the pectoralis major in a young woman, with initial clinical findings mimicking a breast mass. We present the radiographic, immunohistochemical, and molecular workup leading to the correct diagnosis, with review of the differential diagnosis.